On the Molecular Evolution of Leptin, Leptin Receptor, and Endospanin - Londraville, Richard Lyle; Prokop, Jeremy W.; Duff, Robert Joel; Liu, Qin; Tuttle, Matthew (Frontiers in Endocrinology, 2017)
Over a decade passed between Friedman’s discovery of the mammalian leptin gene (1) and its cloning in fish (2) and amphibians (3). Since 2005, the concept of gene synteny conservation (vs. gene sequence homology) was instrumental in identifying leptin genes in dozens of species, and we now have leptin genes from all major classes of vertebrates. This database of LEP (leptin), LEPR (leptin receptor), and LEPROT (endospanin) genes has allowed protein structure modeling, stoichiometry predictions, and even functional predictions of leptin function for most vertebrate classes. Here we apply functional genomics to model hundreds of LEP,LEPR,and LEPROT proteins from both vertebrates and invertebrates. We identify conserved structural motifs in each of the three leptin signaling proteins, and demonstrate Drosophila Dome protein’s conservation with vertebrate leptin receptors. We model endospanin structure for the first time and identify endospanin paralogs in invertebrate genomes. Finally, we argue that leptin is not an adipostat in fishes, and discuss emerging knockout models in fishes.